Upaya Meningkatkan Kemampuan Guru dalam Menerapkan Pembelajaran Berdiferensiasi Melalui Strategi Discovisit - Siska Yuniyati (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2024)
Each student brings their own uniqueness which teachers must address by organizing learning that can accommodate all the learning needs of each student. Differentiated learning is a solution to ensure that every student gets a learning environment that supports the growth and development of their potential, interests and abilities. This is a challenge for school principals as service delivery managers to ensure the implementation of differentiated learning. The principal uses the discovisit strategy to improve teachers’ abilities in implementing differentiated learning. The aim of this research is to describe the application of the discovisit strategy to improve teachers’ abilities in implementing differentiated learning and determine the increase in teachers’ abilities in implementing differentiated learning through the discovisit strategy. The subjects of this research were 6 class teachers, at Mulur 01 State Elementary School, Bendosari District, Sukoharjo Regency. The results of this good practice show that the discovisit strategy is effective in increasing teachers’ abilities in implementing differentiated learning and there has been an increase in teachers’ abilities in implementing differentiated learning, from initially an average academic supervision score of 69.31 increasing to 96.45 in the very good category.